2022
DOI: 10.3127/ajis.v26i0.3833
|View full text |Cite
|
Sign up to set email alerts
|

When robots join our team: A configuration theory of employees’ perceptions of and reactions to Robotic Process Automation

Abstract: Robotic process automation (RPA) as a lightweight automation technology has witnessed an increasing uptake in the industry in recent years. Despite considerable changes in employees’ tasks and processes brought about by the introduction of RPA, there is a lack of research that explores how employees react to an RPA implementation. Hence, the goal of this research is to understand employees’ perceptions of and reactions to RPA as these affect their interaction with the technology and, ultimately, their adoption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…This is because automation of routine work with RPA has consequential impact on work and workplaces, leading to changes in organisational structures and redesigned roles for human employees (Staaby et al, 2021). A few studies that pay attention to impacts of RPA on human employees suggest that changes as a result of an RPA implementation take place through an emergent, relational process that involves interactions between the technology, the organisation-centric approach enacted by managers and developers, and human employee responses to software robots (Andersson et al, 2022; Seiffer et al, 2021; Staaby et al, 2021; Waizenegger and Techatassanasoontorn, 2022). However, there is a lack of research that pays close attention to how key organisational participants, including developers, managers and employees, engage with RPA and shape the dynamics of changes to work and workplaces.…”
Section: Robotic Process Automationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because automation of routine work with RPA has consequential impact on work and workplaces, leading to changes in organisational structures and redesigned roles for human employees (Staaby et al, 2021). A few studies that pay attention to impacts of RPA on human employees suggest that changes as a result of an RPA implementation take place through an emergent, relational process that involves interactions between the technology, the organisation-centric approach enacted by managers and developers, and human employee responses to software robots (Andersson et al, 2022; Seiffer et al, 2021; Staaby et al, 2021; Waizenegger and Techatassanasoontorn, 2022). However, there is a lack of research that pays close attention to how key organisational participants, including developers, managers and employees, engage with RPA and shape the dynamics of changes to work and workplaces.…”
Section: Robotic Process Automationmentioning
confidence: 99%
“…Despite a few studies that take on a human employee’s perspective to understand impacts of RPA on their work (Andersson et al, 2022; Seiffer et al, 2021; Staaby et al, 2021; Waizenegger and Techatassanasoontorn, 2022), IS research has yet to develop empirically grounded theoretical artefacts (Lowry et al, 2020) with a broader perspective to explain how key organisational participants including developers, managers and employees engage with this new digital technology and shape the dynamics of change and transformation of work. Previous studies found that managers and developers play an important role in driving changes induced by a new digital technology implementation (Andersson et al, 2022; Hekkala et al, 2018; Staaby et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Robotic Process Automation (RPA) is a key technology of Industry 4.0 [4,28], involving intelligent network integration of machines and processes [1,23]. RPA leverages software bots to automate repetitive business processes that are traditionally performed by humans [8,32,33]. Currently, RPA-identified as one of the easiest, least invasive, and fastest automation approaches-is gaining increasing significance [33].…”
Section: Introductionmentioning
confidence: 99%
“…RPA leverages software bots to automate repetitive business processes that are traditionally performed by humans [8,32,33]. Currently, RPA-identified as one of the easiest, least invasive, and fastest automation approaches-is gaining increasing significance [33]. Compared to previous digital transformation technologies [22], RPA can be implemented swiftly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation